A study on an appropriate model of law on human embryo stem cell research in Malaysia / Nurlina Rahim, Nur Hamizah Adenan and Mohd Azhier Farhan Arisin - Rahim, Nurlina; Adenan, Nur Hamizah; Farhan Arisin, Mohd Azhier (Faculty of Law, 2012)
Stem cells which are characterized by its ability to differentiate into specific cells are highly regarded by the scientific community as providing possible treatment for degenerative diseases. Owing to such great advantage to human race, scientific communities around the world have been conducting many research involving human embryonic stem cells. But the popularity of human embryonic stem cells has not only sparks interest among scientific community but also controversial among legislatures due to the employment of method which requires human embryos to be destroyed for extraction of the stem cells. The law to regulate the practices of human embryonic stem cells research among scientist is therefore inevitable to safeguard human subjects from malpractices by research community. The scantiness of proper mechanism to monitor and regulate the practices of human embryonic stem cells research has prompted for a specific legislation to be enacted in Malaysia. This research paper is therefore aims firstly to analyze the lacunae in Malaysia's regulatory scheme, secondly to study the legislative model of law on stem cell research in the United Kingdom and in the United States of America for lesson to be learned and lastly to make recommendations as to which model of law suits Malaysia in the matter of stem cells research. In using largely legislative materials from the UK and the US as well as scholastic journals, this research paper increases understanding of the legal approach in the UK and the US as well as the position in Malaysia.